Peran Penelitian Tindakan Kelas dalam Meningkatkan Kompetensi Mengajar Guru - Mantasiah R; Amir Amir (Universitas Negeri Makassar, 2018)
Education always leads to the improvement of competence and qualifications of educators. Therefore,teachers as educators who are assigned to educate the next generation must have professional qualifications in theirrespective fields. As professional educators, both teachers and school principals are required not only to carry outthe tasks of managing, educating and teaching, but also must develop their professionalism. To be a professionaleducator, a teacher should be able to plan, carry out processes, assess learning outcomes, conduct guidance andcoaching, as well as conduct research and community service. One way to develop the teaching profession, theteacher must be able to make scientific work by conducting research activities. Many problems in learning that needsolutions, and one of the ways to improve the quality of learning is the teacher must carry out classroom actionresearch.